2006
DOI: 10.2459/01.jcm.0000215273.70391.bf
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilization after pacemaker implantation

Abstract: The present study shows that an early mobilization protocol is feasible because no statistical differences resulted from the two groups of study as regards clinical outcome, complications and electronic measurements of the implanted devices, which have been followed up for 2 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…A study of early, supervised shoulder mobilization immediately after artificial pacemaker implantation did not observe any device complications. 353…”
Section: Resistance Trainingmentioning
confidence: 99%
“…A study of early, supervised shoulder mobilization immediately after artificial pacemaker implantation did not observe any device complications. 353…”
Section: Resistance Trainingmentioning
confidence: 99%
“…Among more recent studies, in 2003 the retrospective study by Villaba et al 16 included both hospitalized patients and outpatients undergoing CIED procedure and did not found an higher rate of complications in patients mobilized early. In 2005 Miracapillo et al 17 published the unique randomized trial available in literature on early mobilization after CIED procedure: they randomized 134 patients into 2 groups (early and late mobilization) finding no significant differences as to complication rates. In that study patients were not equally divided (because 57 were allocated in early mobilization group and 77 in the standard group), furthermore patients were followed-up for 2 months.…”
Section: Discussionmentioning
confidence: 99%
“…29 Dowling et al 24 also found no difference in hematoma formation among patients ambulated 3 hours after angiography. In a study by Miracapillo and colleagues, 26 there were no statistical differences in hematoma rates, lead displacement, or high-pacing thresholds between patients mobilized 3 hours after pacemaker implantation compared with those mobilized after 24 hours. However, a study found that 10% of its patients who had undergone angioplasty required more prolonged bed rest at 4 hours.…”
Section: Safety Of Mobilizing Patients Following Cardiac Proceduresmentioning
confidence: 90%
“…[19][20][21][22][23][24][25][26][27][28][29][30][31] Specifically, the safety of early ambulation after coronary catheterization procedures has received attention. These studies assessed the safety and efficacy of early ambulation compared with standard protocols, based on the presence of complications such as bleeding, hematoma, and pseudoaneurysm.…”
Section: Safety Of Mobilizing Patients Following Cardiac Proceduresmentioning
confidence: 99%